2019
DOI: 10.15406/jcpcr.2019.10.00388
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards testicular self-examination among regular undergraduate non-health sciences university students, Debre Tabor, Amhara Regional State, North West Ethiopia

Abstract: Background: Testicular self-examination is a screening technique that involves inspection and palpation of the testes for early detection of testicular cancer. The incidence of testicular cancer among 15-35 aged males have increased worldwide though being rare in the general population. In spite of increase, nine out of ten testicular cancer cases can be detected by testicular self-examination and almost 90% can be cured if earlier detected. The aim of this study was to assess knowledge, attitude and practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
6
7
0
Order By: Relevance
“…In the current study, out of 402 respondents, the majority (56.7%) of the respondents had poor knowledge. This finding is in line with other study findings from (53%) Ethiopia [ 14 ] and (53%) Bahrain [ 15 ]. This was lower than other related studies conducted (90%) in London [ 16 ] and (61.36%) in Saudi Arabia[ 11 ], although it is greater than the study findings (44%) from Turkey [ 17 ] and (41.2%) Uganda [ 6 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the current study, out of 402 respondents, the majority (56.7%) of the respondents had poor knowledge. This finding is in line with other study findings from (53%) Ethiopia [ 14 ] and (53%) Bahrain [ 15 ]. This was lower than other related studies conducted (90%) in London [ 16 ] and (61.36%) in Saudi Arabia[ 11 ], although it is greater than the study findings (44%) from Turkey [ 17 ] and (41.2%) Uganda [ 6 ].…”
Section: Discussionsupporting
confidence: 94%
“…This variation might be due to the higher awareness and screening practice in developed countries compared to that of underdeveloped or developing countries. Likewise, in this study, 45.8% knew the most common signs and symptoms of TC, which is a higher figure than the study findings (23.56%) of Saudi Arabia [ 11 ], same line with the study findings (38.3%) of Turkey [ 17 ], and lower than the study findings (15%) from Bahrain [ 14 ]. In this study, regarding risk factors, 54.7% gave correct responses on family history, 58% on age, and 62.8% on prior trauma, and these findings are in contrast with the findings of Saudi Arabia which [ 11 ] shows family history of TC 29.38%, age 14.06%, and prior trauma 38.19%.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The majority of men in this study were willing to perform TSE on a regular basis but more than half had never done it before and reported lack of knowledge on how to do TSE. These results are consistent with previous literature, which shows low knowledge of TSE amongst males [23,35,37,[48][49][50][51][52]. The fact that approximately 10% of the men in the current study were shown by a doctor how to perform TSE indicates a serious gap in a potential source of education on TSE.…”
Section: Discussionsupporting
confidence: 92%
“…Brenner et al [54] also reported that fewer than half of the pediatric residents educate patients on TSE since they believe it can cause excess anxiety. Increased TSE awareness training for physicians, nurses, GPs and public health o cers has been shown to decrease delay in the diagnosis of TC and improve disease-free survival [17,52,56,58]. This is important because physician recommendation on TSE practice has been found to have striking success, with men who reported a physician recommendation for TSE having at least six times higher odds of performing regular TSE compared with those who reported no such recommendation [59].…”
Section: Discussionmentioning
confidence: 99%